Amazing grace: Vancouver's supervised injection facility granted six-month lease on life - Small Dan (BMC, 2008)
Abstract Addiction should be a matter, primarily, for the Chief of Medicine rather than the Chief of Police. While internationally renowned for its social kindness, Canada has not been without its share of disgraceful political mistakes in the not too distant past. Regrettably, there are many shameful events in Canada that have unfolded in the name of public policy including the banishment without medical treatment of Chinese Canadians living with leprosy to die on D'Arcy and Bentinck Islands in British Columbia while European Canadians stricken similarly enjoyed healthcare on the mainland as well as the eternally haunting treatment of people of aboriginal ancestry who were without full voting privileges in some parts of Canada until 1965 and abandoned to encampments, reserves, that paralleled South African apartheid. In due course, these public policies have come to be understood as horrific in retrospect. Many have all met with a remorseful fate where a future Prime Minister is held to public account for the sad excesses of an earlier generation. With respect to North America's only supervised injection facility (SIF), a medical program aimed at reducing fatal overdoses and infections (HIV, HCV) in injection drug users, Canada's Prime Minister Stephen Harper holds the ability to forestall a similarly heartrending fate in his political hands. The SIF currently has a temporary exemption from Canada's "Controlled Drugs and Substances Act" in order to operate until June of 2008. As such, the fate of the SIF is politically determined each time behind closed doors by the Prime Minister and his ministers. Sadly, the Prime Minister appears lost at present, content to ignore the scientific and medical evidence on the matter of population health. In light of the vast medical evidence accumulated on Vancouver's SIF, the fate of injection facilities needs to be taken out of the political realm entirely. I am hoping that the Prime Minister will be found, see the light of the scientific evidence, and lead the way towards to provision of a permanent medical exemption for injection facilities from Canada's Controlled Drugs and Substances Act (CDSA). In so doing, the Prime Minister would be on the brink of grace and would rescue a life saving health program from perpetual political interference.